2022
DOI: 10.3390/nano12040585
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Integration of Functionalized N-rGO-Ni/Ag and N-rGO-Ni/Co Nanocomposites as Synergistic Oxygen Electrocatalysts in Fuel Cells

Abstract: Fabrication of composites by developing simple techniques can be an efficient way to modify the desire properties of the materials. This paper presents a detailed study on synthesis of low cost and efficient nitrogen doped reduced graphene oxide nickle-silver (N-rGO-Ni/Ag) and nickel-cobalt (N-rGO-Ni/Co) nanocomposites as electrocatalysts in fuel cell using one-pot blended reflux condensation route. An admirable correlation in the structures and properties of the synthesized nanocomposites was observed. The Ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…The C 1s spectra in Figure 4a showed that the peaks of the precursor at 284. 14 [22,43,44]. With an increase in calcination temperature, the peak intensity related to oxygen functional groups in Ni/rGO decreased significantly and finally gradually disappeared, indicating that the oxygen functional groups of GO were effectively removed after heat treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C 1s spectra in Figure 4a showed that the peaks of the precursor at 284. 14 [22,43,44]. With an increase in calcination temperature, the peak intensity related to oxygen functional groups in Ni/rGO decreased significantly and finally gradually disappeared, indicating that the oxygen functional groups of GO were effectively removed after heat treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Not only do they support metal nanoparticles (NPs), but they also facilitate electron/mass transfer and stability through metal-support interactions (MSI) [13]. Among them, graphene materials possess high specific surface areas, excellent conductivity, and adequate porosity [14,15]. They can achieve uniform dispersion of metal NPs through high electrochemically active surface areas, thereby maximizing the utilization of active metals and providing more active sites for catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical impedance spectroscopy presents that NC-1000 possesses a smaller charge transfer resistance compared with Pt/C in Figure S8, clearly suggesting that NC-1000 has an excellent charge transport performance. [44][45][46][47] The results indicate that NC-1000 catalyst can provide more quicker reaction kinetic and support the outstanding inherent ORR activity, which is favorable evidence for rapid charge/mass transformation due to hierarchical pore constitution. [48][49][50][51][52]…”
Section: Resultsmentioning
confidence: 99%